Governing Machine Learning Pipelines Through Codified Compliance and Automated Auditability in MLOps Ecosystems - Nolan F. Wexford (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
The rapid institutionalization of machine learning within enterprise decision-making has transformed software systems into socio-technical infrastructures whose outputs increasingly shape regulatory exposure, organizational accountability, and public trust. As machine learning models are embedded into automated workflows, traditional compliance mechanisms rooted in documentation and retrospective auditing are proving inadequate to manage the velocity, opacity, and adaptive behavior of modern MLOps pipelines. This research article advances a theoretically grounded and empirically informed argument that compliance itself must be re-engineered as executable infrastructure within machine learning systems. Drawing on recent scholarship in MLOps, DevOps, software architecture, and algorithmic governance, this work proposes a conceptual synthesis in which regulatory requirements, audit controls, and traceability are operationalized as code within continuous delivery pipelines. The notion of compliance-as-code is analyzed through the lens of automated audit trails, pipeline orchestration, and cloud-native governance frameworks, with particular attention to the implications of embedding regulatory logic directly into machine learning lifecycle management, as articulated by recent work on HIPAA-as-Code in cloud-based SageMaker pipelines (European Journal of Engineering and Technology Research, 2025). Methodologically, the article employs a theory-driven qualitative synthesis of extant literature combined with interpretive analysis of contemporary pipeline architectures. This approach allows the research to articulate not merely how compliance-as-code is implemented, but why it represents a fundamental shift in how organizations conceptualize trust, risk, and responsibility in algorithmic systems. The results demonstrate that automated auditability transforms regulatory compliance from a bottleneck into a continuous control layer that operates in parallel with model training, deployment, and monitoring, thereby enabling scalable governance without sacrificing agility (European Journal of Engineering and Technology Research, 2025; Zaharia et al., 2018). The discussion section situates these findings within ongoing scholarly debates about AI accountability, MLOps maturity, and socio-technical risk management, revealing both the transformative potential and the unresolved tensions of codified compliance. Ultimately, this article argues that the future of trustworthy artificial intelligence will be determined not only by model accuracy but by the degree to which regulatory and ethical constraints are natively embedded within the computational substrates of machine learning systems.